Pressure-mediated mechanosensitive Piezo2 channel is activated in neurogenic bladder and promote bladder fibrosis in children - Lei Lv; Yanping Zhang; Qi Li; Junkui Wang; Shuai Yang; Zhaokai Zhou; Shuai Li; Zhengguang Zhang; He Zhang; Xingchen Liu; Yibo Wen; Jian Guo Wen (Journal of Molecular Medicine, 2026)

Upcycling lignocellulosic biomass using a radial-axial fixed-bed ex-situ catalytic pyrolysis reactor - Fuzheng Li; Jinping Guo; Xingshan Shi; Weiling Piao; Cristina Franch; Yanping Chen; K. Seshan; Songbo He (Bioresource Technology, 2026)

Coordinate-preserving degradation-knee mapping for Kriging relevance mechanisms in FFD-based hull-form optimization - Qingwen He; Yanping He; Zhe Chen; Xin Yu; Jintao Zhou (Ocean Engineering, 2026)

Numerical investigation on the flow field characteristics and the effect of column boot clearance angle on hydrodynamic performance of deep-draft cylindrical offshore platforms - Chengming Qin; Zhe Chen; Yanping He; Yadong Liu (Ocean Engineering, 2026)

Potential of biofortification with tissue-adhesive exopolysaccharide-producing Lactiplantibacillus plantarum to fine-tune microstructure, stabilize texture and color, and enrich flavor of radish Paocai during fermentation - Yuli Huang; Haimei Lai; Yali Wang; Jiaqi Liu; Mengting Liu; Yanping He; Lihong Ge; Nan Zhao (Food Bioscience, 2026)

Dual-responsive and CD44-targeted nanotherapy to remodel the fibrotic niche for reversing liver fibrosis - Jingwei Li; Jiahao Chen; Lingling Wang; Wei Zhao; Yan Xia; Jinhang Zhang; Jie Zhou; Haiying Song; Xinghe Ji; Zijing Zhang; Shuting Qiu; Xiandan Jing; et al. (Chemical Engineering Journal, 2026)

Room-temperature photoinduced synthesis of ultrabright silanized polymer dots for ultrasensitive miRNA-21 detection in lung cancer diagnosis - Peipei Hu; Yunpeng Xue; Jianlin Yu; Yang Wu; Haoxuan Xiong; Tingting Miao; Dan Wang; Qinghua He; Yanping Li; Zhenqiang Ning (Chemical Engineering Journal, 2026)

Parametric investigation of roll damping for a polar icebreaker using CFD and free-decay experiments - Wei Zhang; Yadong Liu; Yanping He; Chengming Hao; Hanyi Yao; Houfei Wu (Ocean Engineering, 2026)

Molecular Analysis of a New Alphapartitivirus from Rhizoctonia solani AG-4 HG III Isolate Rs292 - Yangyang Li; Yanping He; Hongyang Chu; Wenli Li; Hongyu Wang; Yi Chen; Churong Wu; Yanqiong Li (Current Microbiology, 2026)

Salvianolic Acid A Relieves Acute Lung Injury by Promoting the Expression of FOXO1 and Activating Autophagy Through the Inhibition of miR-217-5p - Xia Liu; Yanping Shi; Li Huang; Hongbo Chen; Raofei Fan; Hongzhong Zhang; Qiaofen Li; Na Yan; Maiding He; Yonghua Yang (Biochemical Genetics, 2026)

Integrated Application of Iso-Seq and RNA-Seq Analyses to Uncover Genes Involved in Ovarian Development in Platypharodon extremus - Zhuoyu Yang; Yanping Zhang; Wei Ka; Wenjing He; Yujie Yang; Wenlong Jiao; Jianlin Wang (Fishes, 2026)
This study focused on Platypharodon extremus, a species endemic to the Qinghai–Tibet Plateau, and systematically analyzed its reproductive biology, sex steroid hormones, ovarian histology, and transcriptomic characteristics throughout its complete reproductive cycle (August 2020 to June 2021). The results demonstrated that the body length, height, body weight, and gonadal weight of female individuals continuously increased with age, while the Gonadosomatic index (GSI) was lowest during the breeding season (June–August) and gradually rose during the non-breeding period. Serum estradiol (E2) and progesterone (P4) exhibited rhythmic fluctuations corresponding to ovarian development: E2 rose from 25.77 ng/L in stage-I to 146.00 ng/L in stage-V, then declined post-ovulation; P4 increased from 59.88 pmol/L in stage-I to 239.03 pmol/L in stage-V, showing a significant decrease after ovulation. Histological observations classified ovarian development into stages I–VI, clearly delineating the complete process from oogonium proliferation, cortical vesicle formation, yolk accumulation, maturation to postpartum regression. To explore molecular changes during the transition from vitellogenesis to oocyte maturation, we built a reference transcriptome with 30,060 non-redundant transcripts (average length = 1975 bp) using PacBio and Illumina data, and 91.87% of these transcripts received functional annotation hits against public databases. A comparative differential expression analysis was performed between ovarian stage III (active yolk accumulation) and stage V (oocyte fully matured). A total of 11,324 differentially expressed genes were identified (5249 upregulated and 6175 downregulated) between these two stages. GO enrichment analysis revealed predominant involvement in cellular processes, cellular components, and catalytic activities, while KEGG analysis demonstrated significant enrichment in metabolic pathways, PI3K-Akt, MAPK, and calcium signaling pathways. Quantitative PCR (qPCR) validation confirmed that candidate genes, including pik3a, calm, mapk1 map2k ddx49, and igf2 were significantly upregulated at stage V. These differentially expressed genes (DEGs) may represent potential molecular signatures linked to the transition from vitellogenesis to oocyte maturation. Our integrated transcriptomic and qPCR data identify potential gene candidates involved in ovarian maturation; however, these findings reveal correlation rather than direct regulatory causality. This study offers fundamental data and theoretical insights for understanding the reproductive regulatory mechanisms and aquaculture management of this endemic species.

Mining and characterization of endogenous constitutive promoters in Aspergillus oryzae - Sha Huang; Laimao Luo; Jingyin Zhou; Zhui Tu; Qinhua He; Yanping Li (Food Bioscience, 2026)

Single-nucleus RNA sequencing reveals a spatiotemporal pattern of H2S signaling in Chinese cabbage - Jiao Zhang; Yang Chen; Bo Liu; Yuwei Qin; Yue Luan; He Yin; Wenqi Liu; Limei Chen; Jixian Zhai; Yanxi Pei; Yanping Long; Zhuping Jin (Science China Life Sciences, 2026)

Narirutin Mitigates Dextran Sodium Sulfate-Induced Enteritis in Procambarus clarkii by Modulating Intestinal Microbiota - Jian Li; Yitian Chen; Yanping Cai; Huiling Zhang; Bin Qiu; Xingfei Huang; Yan Wen; Aimin Wang; Bin He; Yude Wang; Shaojun Liu (Fishes, 2026)
Enteritis is a disease that affects Procambarus clarkii, significantly impacting aquaculture due to its high incidence and mortality rates, resulting in economic losses. Currently, the molecular mechanisms behind enteritis in Procambarus clarkii are not well understood. In this study, we established a model of intestinal inflammation induced by dextran sodium sulfate (DSS). Subsequently, histopathological changes, transcriptome analysis, intestinal microbiota analysis and immunofluorescence analysis were conducted. Histopathology showed that after treatment in the DSS + Narirutin (NR) group, there was an improvement in intestinal inflammation, and the structure of the intestinal tissue was partially restored. The intestinal transcriptome analysis revealed that in the DSS + NR group, 234 genes were upregulated and 188 genes were downregulated after treatment. This indicates a significant change in gene expression. KEGG enrichment analysis revealed that the DEGs were significantly enriched in TGF-β signaling pathway and PI3K-Akt signaling pathway. The results from 16S rRNA sequencing showed that in the DSS + NR group, the relative abundance of Akkermansia muciniphila significantly increased. Immunofluorescence results showed that, compared to the control group, the expressions of Occludin, nuclear factor-kB-p65 (NfkB-p65), Zonula occludens-1 (ZO-1), and Claudin-1 decreased following DSS treatment. However, treatment with NR was able to inhibit these changes. This further validated that NR can alleviate enteritis in Procambarus clarkii.

Genetic Basis of α-1,3 Galactose Epitopes in Animal Reservoirs of Coronaviruses - Xinjia Mai; Chenxi Zhu; Yu He; Nian Wang; Yue Ma; Wen Zhang; Yanping Wang; Yunsen Li; Dapeng Zhou (Phenomics, 2026)

Influence of bow configuration on brash ice resistance: Comparison of invisible and conventional bulbous bows - Jianmei Chen; Zhe Chen; Yanping He (Ocean Engineering, 2026)

Therapeutic potential of Lactobacillus kefiranofaciens ZW18 postbiotic in alleviating hepatocellular carcinoma - Hanxue Xu; Weitao Geng; Jiangye He; Longgang Jia; Gang Zhao; Yanping Wang (Food Research International, 2026)

Novel Hybrid Peptide ML-2 with Antibacterial and Antibiofilm Activity Against Pseudomonas aeruginosa - Shenghua Wu; Yanping Shi; Yang He; Tao Zhang; Feilong Chen; Yingchun Zhang; Tao Wang (Current Microbiology, 2026)

Climate-sensitive environmental drivers shaping epipelagic and mesopelagic fauna biodiversity patterns in the Amundsen–Bellingshausen Seas, Southern Ocean - Jiayu Fan; Yang Liu; Yanping Luo; Yuru Li; Mi Duan; Chunlin Liu; Zhenjiang Ye; Jianchao Li; Peng Sun; Chi Zhang; Jun Zhao; Jianfeng He; et al. (Environmental Research, 2026)

Mitigating intrinsic defects and optimizing interfacial energetics via aluminum-doping toward 13.6% efficiency kesterite solar cells - Xinyu Zhang; Jingyi Meng; Zhenyan He; Chun Guo; Linxin Gao; Yanping Song; Wenjie Zhu; Sisi Jia; Busen Zhai; Lunkan Shen; Dipeng Xu; Huanhuan Sun; et al. (Chemical Engineering Journal, 2026)

Integrated morphological, transcriptomic, and metabolomic profiling reveals differential development mechanisms in two weeping forsythia genotypes during tissue culture - Yanxia He; Yanping Zheng; Jiaqi Geng; Yue Wang; Na Qi; Xu Lu; Xiaoxiao Wang; Yongjin Sun; Helong Wen; Xiaoya Liu; Xin Sun; Xianping Wang; et al. (Physiology and Molecular Biology of Plants, 2026)

Railway CORS GNSS PWV forecasting using normal time-frequency transform and deep learning with transfer learning strategy - Chen Chang; Yanping Liu; Yong Wang; Yunlong Zhang; Xiangshun Meng; Haozhe Chi; Chunrui He (Advances in Space Research, 2026)

Numerical Study on the Effect of Column Boot Diameter-to-Height Ratio on the Hydrodynamic Performance of Deep-Draft Cylindrical Offshore Platforms - Chengming Qin; Zhe Chen; Yanping He; Yadong Liu (Journal of Marine Science and Engineering, 2026)
For deep-draft cylindrical platforms with a large annular column boot, the influence of the column boot diameter-to-height ratio (d/h) on motion performance remains unclear. This study investigates the effect of d/h on platform hydrodynamics while keeping the main body geometry, displacement, and draft unchanged. A hybrid numerical model validated against tests is adopted: STAR-CCM+ free-decay simulations identify equivalent linear damping, and ANSYS AQWA predicts hydrodynamic coefficients, response amplitude operators, and coupled time-domain responses under a 100-year survival sea state in the western South China Sea. Increasing d/h substantially increases heave added mass and added pitch moment of inertia, leading to longer natural periods and higher damping in heave and pitch. However, its effect on motion responses is non-monotonic and strongly response-dependent. As d/h increases, the responses are initially reduced markedly. The minimum surge and heave responses occur at d/h = 2.39 and 4.67, with reductions of about 34.0% and 87.2%, respectively, while the pitch response is already reduced by about 67.3% at d/h = 7.22. Further increases in d/h may weaken surge and heave mitigation while providing limited additional benefit for pitch. These findings provide qualitative understanding and quantitative guidance for response-oriented column boot design and optimization of similar platforms.

The insecticidal activity and mechanism of the Cinnamomi ramulus (Lauraceae) essential oil against Tribolium confusum Jaquelin Du Val, 1868 (Coleoptera: Tenebrionidae): insights from transcriptomic and metabolomic profiles - Qianqian Lian; Jianji Zhao; Yiqing Li; Hui Tang; Yanping He; Qiuling Tang; Wei Zhang; Jie Bi (Journal of Stored Products Research, 2026)

Long-distance lateral migration, accumulation and dissipation of natural gas in the northeastern Ordos Basin, China - Yang Qin; Chiyang Liu; Junfeng Zhao; Faqi He; Wei Zhang; Yanping Ma; Lihua Yang; Deyong Shao; Nan Du; Fuyu Chen (Gondwana Research, 2026)

Improving slurry flow predictions in horizontal pipes: A modification to the Burns turbulent dispersion force model - Weihuang Liu; Yanping He; Mingzhi Li; Hongbo Zhu; Minmin Zheng (Ocean Engineering, 2026)

CoOOH-based colorimetric aptasensor with dual cascade amplification for ultrasensitive monitoring of fleroxacin in honey - Yanping He; Peixuan Li; Xin Zhao; Dongmei Wang; Fuqiang Zhang (Food Control, 2026)

Experimental study of lining temperature field combined effect of heat exchangers and mechanical ventilation - Mingrui Luo; Zuobing Yuan; Liangliang Tao; Yanhua Zeng; Chuan He; Yanping Yuan (Tunnelling and Underground Space Technology, 2025)

Dynamic response analysis of topside transportation using SPMT - Ming Qiu; Min Zeng; Mingzhi Li; Yibin Lv; Changwei wan; Zhengang Wang; Yanping He (Ocean Engineering, 2025)

Overexpression of CYP6CY36 and CYP380C34 contributes to metabolic resistance of Myzus persicae (Sulzer) to flupyradifurone - Qiuling Tang; Jinfeng Hu; Chengfeng Zheng; Wei Zhang; Jie Bi; Yanping He (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Trophic status impacts the potential significance of anaerobic methane oxidation driven by multiple electron acceptors in Lake Taihu sediments - Wangting Yang; Qinan Hu; Hechen Huang; Jinghao Jin; Bingjie Ren; Sile Wen; Yuling Yang; Yefan He; Yanping Wang; Yanan Bai; Yuzhi Song; Lidong Shen (CATENA, 2025)

Population pharmacokinetic characteristics of tacrolimus in Chinese lung transplant recipients and optimisation of dosing regimen during the early post-transplantation phase - Shouning Zhou; Qiaoyan Lian; Huilong Luo; Hui Xie; Yanping Guan; Jianxing He; Li Wei; Chunrong Ju (European Journal of Clinical Pharmacology, 2025)

Polysaccharides from Actinidia Lindl.: Extraction, bioactivities, and emerging applications in food and pharmaceutical industries - Lihao Wang; Chenqing Dong; Qian Wang; Chi Teng; Wuyou Gao; Yujia He; Jun Liang; Yonggang Xia; Haixue Kuang; Yanping Sun (Trends in Food Science & Technology, 2025)

Editorial Expression of Concern: The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2025)

The mechanisms of MTOCs maturation in human and mouse oocytes - Hao Gu; Ling Wu; Mingru Yin; Xingzhu Du; Jing Fu; Fangzhou Xu; Zhiqi Ye; Xuelin Zhang; Huixia Jing; Yuxi Luo; Wenzhi Li; Xiaoxi Sun; et al. (Science Bulletin, 2025)

Homogeneous bioluminescent immunosensor for aflatoxin B1 detection via unnatural amino acid-based site-specific labeling - Mengna Chen; Yanping Li; Qinghua He; Junjie Zeng; Xiaojiang Li; Zhui Tu (Food Control, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Monotonic simple shear characteristics of K 0 highly over-consolidated and remolded Wenzhou clay - Zheng Yu; Yanping He; Hao Wu; Lin Guo (Marine Georesources & Geotechnology, 2025)

Mn-doped copper slag with oxygen vacancies boosts peroxymonosulfate activation for ofloxacin rapid removal - Linjin Li; Yaoze Wang; Guangfei Qu; Nanqi Ren; Yanping Liu; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Yingying Cai; Xiaofei Li; Rui Xu (Journal of Water Process Engineering, 2025)

Trapping phenylacetaldehyde by litchi shell polyphenols and their characteristic catechins in chemical model and roast pork patty: Identification of catechins-adducts and toxicity assessment - Qi Chen; Yanping Xian; Ming Liang; Min Qian; Qingping Wu; Qi He; Xiaofang Zeng; Weidong Bai; Hao Dong (Food Chemistry, 2025)

The independent and joint effects of meteorological factors on influenza: A nationwide time series study in China - Mengen Guo; Yunfei Zhang; Jianxiong Hu; Aga Zheng; Guanhao He; Xiaokun Yang; Hongting Zhao; Tao Liu; Fengrui Jing; Ziqiang Lin; Yanping Zhang; Maigen Zhou; et al. (Urban Climate, 2025)

Alkaline-thermal synergistic activation of persulfate for sawdust hour-level humification to prepare fulvic-like-acid fertilizer - Dongfang Wang; Xinyan Chen; Jing Zhang; Jia Xu; Xianghai Kong; Jinghong Ye; Rongjun Zhang; Huiqun Fan; Li Liu; Xiuping Zhan; Yan Qin; He Xu; et al. (Bioresource Technology, 2025)

Impact of conversion of coastal wetlands into paddy fields on the process of nitrite-dependent anaerobic methane oxidation - Qinan Hu; Weiqi Wang; Wangting Yang; Yuling Yang; Yanan Bai; Yefan He; Bingjie Ren; Yanping Wang; Jinghao Jin; Lidong Shen (Soil Ecology Letters, 2025)

Inhibition effect and mechanism of hydrocolloids on the formation of heterocyclic aromatic amines (HAAs) in meat products: A review - Xiaotong Huang; Yanping Xian; Qi He; Qingping Wu; Weidong Bai; Xiaofang Zeng; Hao Dong (Food Chemistry, 2025)

Critical review on food packaging strategy against spoilage - Lei Liu; Youwei Jiang; Kun Wan; Yanping Wei; Du Tuo; Chuanqin Zhou; Quanguo He; Yimin Tan (Food and Humanity, 2025)

Biosynthetic small molecule antigens mimics medicated lateral flow immunoassay for mycotoxin Fumonisin B1 using nanobody fusion proteins - Chong Cai; Yuheng Xia; Yuanzhen Guo; Binhui Huang; Tailong Wei; Yun Liang; Qiannan Gao; Zhui Tu; Yanping Li; Qinghua He (Journal of Hazardous Materials, 2025)

Effects of simulated microgravity on dental pulp stem cell stemness - Huailong Hou; Zhengjun Qiu; Jingyi Che; Yanping Li; Jingxuan Sun; Weiwei Zhang; Jinjie Ma; Shuang Zhang; Mengdi Li; Yumei Niu; Lina He (Journal of Molecular Histology, 2025)

Thermal deformation analysis of the Advanced Space-Based Solar Observatory (ASO-S) in orbit based on payloads measurement - Zhongguang Yang; Lei Deng; Cheng Zhu; Zengshan Yin; Tao He; Yu Huang; Yanping Bai; Hu Jiang; Yong Yang; Ye Zhang; Binglong Chen; Xinyu Li; et al. (Advances in Space Research, 2025)

Automated calibration of Noah-MP land surface model for improved irrigation representation in the North China Plain - Danqiong Dai; Yanping Li; Liang Chen; Fei Chen; Zhenhua Li; Zhe Zhang; Prasanth Valayamkunnath; Li Xu; Cenlin He; Zhuguo Ma (Journal of Hydrology, 2025)

A portable microfluidic platform for ultra-sensitive detection of ovarian cancer biomarkers via cascade signal amplification - Yuzhen Wang; Wenxiu Long; Yanping Wang; Yuanyue Han; Fei Zeng; Jingjing Li; Bangshun He; Yujun Song; Yanfeng Gao (Chemical Engineering Journal, 2025)

Highly degradable bio-based plastic with water-assisted shaping process and exceptional mechanical properties - Jingjing Wang; Yuan Liang; Yuhan Chen; Hai Wan; Wenbin Jin; Ting Luo; Yuwei Chen; Peng Wei; Shuohan Huang; Yong He; Yanping Wang; Yumin Xia (Carbohydrate Polymers, 2025)

Synthesis and Characterization of Efficient Adsorbents for Methylene Blue Based on Graphene Oxide/β-cyclodextrin Composites - Yanping Qu; Hongcui Li; Ibrahim Yakub; Wen He; Wenchan Dong; Mohamad Hardyman Barawi; Sirui Wang; Huimin Ma; Zhenpeng Zhu (Water, Air, & Soil Pollution, 2025)

Dynamic aromatics: Evaluating fragrance quality shifts and implementation of real-time rapid detection in Hedychium cut flowers during senescence - Yiwei Zhou; Qin Wang; Xue Wei; Ting Gao; Farhat Abbas; Fulong Yan; Jingjuan He; Yunyi Yu; Rangcai Yu; Yanping Fan (Postharvest Biology and Technology, 2024)

Research on parametric roll of the polar environmental transport ship based on time-domain Rankine panel method - Wei Zhang; Yadong Liu; Yanping He; Yan Zhou; Dong Wang; Yuying Tang; Jianmei Chen (Ocean Engineering, 2024)

A solar thermoelectric system by temperature difference for efficient removal of chromium (VI) in water and soil - Dongqing Cai; Rongxi Hu; Minxue Guo; Dongfang Wang; Yanping Zhu; Chen Sun; Xinyan Chen; Jinghong Ye; Xianghai Kong; He Xu (Journal of Hazardous Materials, 2024)

Ferrihydrite optimizing Feammox inoculum to enhance ammonia removal from concentrate wastewater through continuous upflow anaerobic sludge blanket (UASB) - Linji Xu; Lin Li; Jianxi Liu; Xingzu Wang; Yanping Zhao; Jujiao Zhao; Li Gu; Qiang He; Xinzhu Wang; Jinhua Zhang (Journal of Environmental Chemical Engineering, 2024)

Experimental investigation on strength characteristics of marine soft clay under monotonic and cyclic loading - Lin Guo; Hao Wu; Yanping He; Hui Li; Yilong Sun (Marine Georesources & Geotechnology, 2024)

Three birds with one stone: Sewage sludge deep-drying in 1 hour using secondary aluminum ash to fabricate bricks - Xianghai Kong; Yanping Zhu; He Xu; Jinghong Ye; Shuang Wang; Heliang Xu; Rongjun Zhang; Hongxia Tang; Dongfang Wang; Dongqing Cai (Water Research, 2024)

Prediction and empirical formula correction for brash ice resistance using CFD-DEM based on invisible bulbous bow ship - Jianmei Chen; Zhe Chen; Dong Wang; Yuqing Zhang; Yanping He (Ocean Engineering, 2024)

New role of radical-induced polymerization: Base/self-heating synergistically activate persulfate to boost food waste humification - Dongqing Cai; Xiaoya Pan; Chengjin Wang; Shihu Shu; Pengjin Zhu; Chunhuo Zhou; Dongfang Wang; He Xu; Yanbiao Liu; Wenhai Chu; Xiang Li; Yanping Zhu (Journal of Cleaner Production, 2024)

Efficient and environmentally friendly uric acid voltametric sensor based on Ni-MOF and carboxylated multi-walled carbon nanotubes nanocomposites - Aiting Chen; Nana Tang; Yanping Wei; Shuting Shi; Chuanqin Zhou; Quanguo He; Jianhua Ding (Journal of Environmental Chemical Engineering, 2024)

Effect of micro-diamond and nano-polycrystalline diamond interfacial microstructure on OLC phase transition - Lifeng Dai; Yanguo Li; Wenqi Luo; He Jia; Yongan Luo; Yanping Yang; Yufei Meng; Xin Han; Wantang Fu; Qin Zou; Yingwei Fei (Chemical Engineering Journal, 2024)

Waste milk-derived biodegradable mulch film fabrication and nutrient slow-release performance evaluation - Yanping Zhu; Bingbing Fu; Pengjin Zhu; Shihu Shu; Dongfang Wang; He Xu; Dongqing Cai (Chemical Engineering Journal, 2024)

Design and numerical simulation of the elastomeric support for the topside modules of an FPSO - Yucu Huang; Yanping He; Yadong Liu; Ming Qiu; Mingzhi Li (Ocean Engineering, 2024)

Review of utilization of bamboo fiber in asphalt modification: Insights into preparation, performance, reinforcement, and challenges - Haibin Li; Songjiang Liu; Fan Yang; Siyu He; Hongjun Jing; Xiaolong Zou; Zhigang Li; Yanping Sheng (Journal of Cleaner Production, 2024)

Simultaneous removal of tetracycline hydrochloride and hexavalent chromium by heterogeneous Fenton in a photocatalytic fuel cell system - Jinghong Ye; He Xu; Xianghai Kong; Yong Zhang; Yuhan Chen; Benji Zhou; Yanping Zhu; Dongqing Cai; Dongfang Wang (Journal of Environmental Management, 2024)

Preparation of ternary composite film TiO2/Fe2O3/Ti3C2 for photoelectrocatalytic degradation of organic pollutants and bacterial inactivation in water - Yanping Ma; Jialin Gu; Xinshang Li; Wenquan Zhou; He Wang; Rui Zhang; Jiangang Jiang (Journal of Environmental Chemical Engineering, 2024)

Differences in Precipitation and Related Wind Dynamics and Moisture and Heat Features in Separate Areas of the South China Sea before and after Summer Monsoon Onset - Chunyan Zhang; Donghai Wang; Kaifeng Zhang; Wanwen He; Yanping Zheng; Yan Xu (Advances in Atmospheric Sciences, 2024)

Metabolomics and microbiome provide new insights into mechanisms of the variations between the larva and adult stages of the Model Beetle Tribolium castaneum (Herbst) - Jie Bi; Lirui Zhang; Yanping He (Journal of Asia-Pacific Entomology, 2024)

Electron transfer mediated photo-Fenton-like synergistic catalysis of Fe,Cu-doped MIL-101 coupled with Ag3PO4: Quantitative evaluation and DFT calculations - Xiaojuan Chen; Liang Yao; Song Xu; Juhua He; Ning Li; Jiaxin Li; Bin Liu; Yanping Zhu; Xin Chen; Hailong Wang; Runliang Zhu (Environmental Pollution, 2024)

Mitochondria targeting photoredox catalyst-induced pyroptosis for enhanced immunotherapy against hypoxic tumor cells - Yanping Wu; Qingsong Liu; Shumeng Li; Wenhao Yu; Huanhuan Fan; Shankun Yao; Weijiang He; Zijian Guo; Yuncong Chen (Chemical Engineering Journal, 2024)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

Fabrication of a straw-based degradable mulch film with magnetically controlled-release glyphosate - Dongqing Cai; Mengjia Cui; Linying Wang; Jinghong Ye; Xianghai Kong; Ruobing Mu; He Xu; Yanping Zhu; Dongfang Wang (Chemical Engineering Journal, 2024)

QTL mapping for agronomic traits in Agropyron Gaertn. CP population at the flowering stage - Yonghe Che; Jing Yang; Yutong He; Nan Song; Yanping Yang; Lai Wei; Xinming Yang; Yannong Zhang; Jinpeng Zhang; Haiming Han; Xiuquan Li; Shenghui Zhou; et al. (Euphytica, 2024)

Aralianudaside A, an unusual skeleton triterpenoid saponin with anti-airway inflammatory activity from Aralia elata - Pengcheng Yin; Haishan Qian; Shaohua Li; Benqin Tang; Juan Wang; Shuai Chen; Guanghui Ni; Fawu Dong; Yanping Li; Feng Huang; Rongping Zhang; Hongping He; et al. (Natural Product Research, 2024)

Study of the wet-towing transportation of an FPSO with elastomeric-supporting topside modules - Yucu Huang; Yanping He; Ming Qiu; Yadong Liu; Mingzhi Li (Ocean Engineering, 2024)

Effects of saline water with different concentrations of calcium and magnesium ions on emitter clogging in drip irrigation integrated water–fertilizer system - Long Zhou; Chenchen Wei; Peiling Yang; Yunkai Li; Lili Zhangzhong; Yanping Su; Xin Wang; Xin He (Irrigation and Drainage, 2024)
The application of saline water in drip irrigation is severely constrained due to its high salt content, which causes precipitation and emitter clogging. Therefore, the effects of calcium and magnesium ions at 100, 150 and 200 mg/L in saline water coupled with humic acid nitrogen fertilizer on emitter clogging were studied. Compared with ground saline water, all treatments significantly increased the emitter clogging risk. In the calcium and magnesium ion treatment groups, clogging fouling increased by 23.94–58.35 and 14.55–51.21 mg/cm 2 , the discharge variation ratio (Dra) decreased by 22%–59% and 14%–49%, and the Christiansen coefficient of uniformity (CU) decreased by 29%–79% and 15%–74%, respectively. Higher ion concentrations caused more clogging. Saline water with a high calcium content caused more clogging. Under similar concentration conditions, the Dra and CU in high magnesium saline water were 9%–32% and 8%–51% higher, respectively. In addition, the increase in magnesium ion concentration changed the crystal form of carbonate, slowed the formation rate of precipitated dirt and significantly reduced the carbonate content by 19%–40%. Our results provide support for the popularization of saline water drip irrigation systems.

Sulfate availability drives the reductive transformation of schwertmannite by co-cultured iron- and sulfate-reducing bacteria - Changdong Ke; Yanping Deng; Siyu Zhang; Meihui Ren; Bingcheng Liu; Jingyi He; Renren Wu; Zhi Dang; Chuling Guo (Science of The Total Environment, 2024)

RNA interference of NADPH-cytochrome P450 reductase increases the susceptibility of Aphis gossypii Glover to sulfoxaflor - Qiuling Tang; Xuchao Li; Yanping He; Kangsheng Ma (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Precise diagnosis of breast phyllodes tumors using Raman spectroscopy: Biochemical fingerprint, tumor metabolism and possible mechanism - Yifan Wu; Yaohui Wang; Chang He; Yan Wang; Jiayi Ma; Yanping Lin; Liheng Zhou; Shuguang Xu; Yumei Ye; Wenjin Yin; Jian Ye; Jingsong Lu (Analytica Chimica Acta, 2023)

ZIF-8-derived hollow carbon polyhedra with highly accessible single Mn-N6 sites as peroxymonosulfate activators for efficient sulfamethoxazole degradation - Yue Zhao; Rui Gao; He Wang; Yanping Sun; Xiaohui Zhan; Lei Chen; Junyan Liu; Huixiang Shi (Chemical Engineering Journal, 2023)

The component of the Chamaecyparis obtusa essential oil and insecticidal activity against Tribolium castaneum (Herbst) - Lirui Zhang; Yu Zhang; Yanping He; Huang Dai; Zaixi Shu; Wei Zhang; Jie Bi (Pesticide Biochemistry and Physiology, 2023)

Kinetic and thermodynamic analysis on preparation of belite-calcium sulphoaluminate cement using electrolytic manganese residue and barium slag by TGA - Weilong He; Rui Li; Yanping Yang; Yu Zhang; Dengpan Nie (Environmental Science and Pollution Research, 2023)

Simulation and experimental research on hydrodynamic performance of fully attached submarine in the surface and near the surface modes - Minmin Zheng; Yadong Liu; Youjiang Wang; Yanping He (Ocean Engineering, 2023)

Enhanced degradation of tetracycline under natural sunlight through the synergistic effect of Ag3PO4/MIL-101(Fe) photocatalysis and Fenton catalysis: Mechanism, pathway, and toxicity assessment - Xiaojuan Chen; Liang Yao; Juhua He; Jiesen Li; Song Xu; Ning Li; Yanping Zhu; Xin Chen; Runliang Zhu (Journal of Hazardous Materials, 2023)

Effects of grazing exclusion on vegetation community characteristics over 22 years in the Zoige alpine meadows from China - Xue Jiang; Li He; Yanping Qu; Banghong Jian; Dongzhou Deng; Mei Liu; Jingtian Yang; Yunlong Ma; Dechao Chen; Yi Huang (Acta Oecologica, 2023)

Simultaneous influence of light and CO2 on phytoremediation performance and physiological response of plants to formaldehyde - Lijun Zuo; Dan Wu; Mengsi Deng; Darui He; Yanping Yuan (Environmental Science and Pollution Research, 2023)

Analysis and realization of the influence of sea ice flexural strength on ice resistance in numerical simulation of icebreaking by icebreaker - Zhe Chen; Yanping He; Yupei Ren; Yadong Liu (Ocean Engineering, 2023)

Ag3PO4-anchored La2Ti2O7 nanorod as a Z-Scheme heterostructure composite with boosted photogenerated carrier separation and enhanced photocatalytic performance under natural sunlight - Xiaojuan Chen; Jieming Chen; Ning Li; Jiesen Li; Juhua He; Song Xu; Yanping Zhu; Liang Yao; Yiqi Lai; Runliang Zhu (Environmental Pollution, 2023)

Numerical analysis of continuous icebreaking performance of icebreakers with different bow types - Yupei Ren; Zhe Chen; Yanping He; Chao Chen; Yadong Liu; Guangyao Zheng (Ocean Engineering, 2023)

Preparation of recyclable and deformable POM microfiber for oil–water separation with nature-inspired top–bottom strategy - Wenbin Jin; Jingjing Wang; Hai Wan; Yuan Liang; Shuohan Huang; Yuwei Chen; Peng Wei; Qun Shao; Yanping Wang; Yong He; Yumin Xia (Chemical Engineering Journal, 2023)

MnOx@N-doped carbon nanosheets derived from Mn-MOFs and g-C3N4 for peroxymonosulfate activation: Electron-rich Mn center induced by N doping - Yue Zhao; Xiaohui Zhan; Yanping Sun; He Wang; Lei Chen; Junyan Liu; Huixiang Shi (Chemosphere, 2023)

In situ transformation of bismuth-containing precursors into ultrathin bismuth nanosheets for enhanced electrochemical CO2 reduction - Aihao Xu; Dong Wei; Xiangyu Chen; Taishun Yang; Yanping Huang; Huibing He; Jing Xu (Chemical Engineering Journal, 2023)

Octahedral silver oxide nanoparticles enabling remarkable SERS activity for detecting circulating tumor cells - Meng He; Jie Lin; Ozioma Udochukwu Akakuru; Xiawei Xu; Yanying Li; Yi Cao; Yanping Xu; Aiguo Wu (Science China Life Sciences, 2022)

Fishery Status and Rebuilding of Major Economic Fishes in the Largest Freshwater Lake in China Based on Limited Data - Yang Liu; Huiyun Fu; Linlong Wang; Li Lin; Gang He; Peifeng Fu; Changlai Wang; Yanping Zhang; Bin Kang (Fishes, 2022)
Poyang Lake, the largest freshwater lake in China, possesses abundant fishery resources, but its fish stock status is still unclear. In this work, the stock status of and fishing efforts of nine major economic fishes in the Poyang Lake were estimated from 2000 to 2019 with a catch-based maximum sustainable yield (CMSY) model based on catch and resilience data. It was further predicted whether the biomass of those fishes could be restored to support maximum sustainable yield (Bmsy) under the policy of “Ten years fishing moratorium in the Yangtze River”. The results showed that goldfish Carassius auratus, grass carp Ctenopharyngodon idella, and black carp Mylopharyngodon piceus suffered from higher fishing efforts and low biomass in the past 20 years; bighead carp Hypophthalmichthys nobilis, yellow catfish Tachysurus fulvidraco, and common carp Cyprinus carpio responded differently to their fishing efforts; silver carp Hypophthalmichthys molitrix, Amur catfish Silurus asotus, and mandarin fish Siniperca chuatsi were underexploited. Six species were overfished in 2019, and their biomass would be expected to recover for sustainable exploitation during the fishing moratorium, except for M. piceus. This study provided a case study of feasible freshwater fishery evaluation in limnetic ecosystems.

Substantial changes of chemical composition and sources of fine particles during the period of COVID-19 pandemic in Taiyuan, Northern China - Yang Wang; Yanping Wen; Yang Cui; Lili Guo; Qiusheng He; Hongyan Li; Xinming Wang (Air Quality, Atmosphere & Health, 2022)

Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

In-situ Detection Method for Microplastics in Water by Polarized Light Scattering - Tong Liu; Shijun Yu; Xiaoshan Zhu; Ran Liao; Zepeng Zhuo; Yanping He; Hui Ma (Frontiers in Marine Science, 2021)
Microplastics (MPs) have become the widespread contaminants, which raises concerns on their ecological hazards. In-situ detection of MP in water bodies is essential for clear assessment of the ecological risks of MPs. The present study proposes a method based on polarized light scattering which measures the polarization parameters of the scattered light at 120° to detect MP in water. This method takes the advantage of in-situ measurement of the individual particles and the experimental setup in principle is used. By use of the measured polarization parameters equipped by machine learning, the standard polystyrene (PS) spheres, natural water sample, and lab-cultured microalgae are explicitly discriminated, and MP with different physical and chemical properties can be differentiated. It can also characterize the weathering of different MP and identify the specific type from multiple types of MP. This study explores the capability of the proposed method to detect the physical and chemical properties, weathering state and concentration of MP in water which promises the future application in water quality sensing and monitoring.

Differential effects of three amendments on the immobilisation of cadmium and lead for Triticum aestivum grown on polluted soil - Shengze Zhang; Lingtong Quan; Yanping Zhu; Jin Yan; Xiaoman He; Jia Zhang; Xiaoming Xu; Zhubing Hu; Feng Hu; Yahua Chen; Zhenguo Shen; Yan Xia (Environmental Science and Pollution Research, 2020)

Establishment and evaluation of a model for predicting 3-month mortality in Chinese patients with hepatic encephalopathy - Yanping Cui; Shan Guan; Jie Ding; Yukai He; Qingfang Li; Sikui Wang; Huiling Sun (Metabolic Brain Disease, 2019)

Probiotic Properties and Cellular Antioxidant Activity of Lactobacillus plantarum MA2 Isolated from Tibetan Kefir Grains - Wei Tang; Chao Li; Zengguo He; Fen Pan; Shuo Pan; Yanping Wang (Probiotics and Antimicrobial Proteins, 2018)

Aboveground and belowground litter have equal contributions to soil CO2 emission: an evidence from a 4-year measurement in a subtropical forest - Qingkui Wang; Youzhi Yu; Tongxin He; Yanping Wang (Plant and Soil, 2017)

Synthesis and biological evaluation of novel anti-hepatitis C virus (HCV) agents: 2-hydroxylphenethyl sulfanyl-oxopyrimidines - Daochun Wu; Yue Feng; Hua Wang; Junfeng Yang; Xian Chen; Yueping Wang; Christopher Cong Lai; Yufang Zhang; Cong Li; Xueshan Xia; Yanping He (Medicinal Chemistry Research, 2017)

Cycloartane-type triterpenoids from Astragalus hoantchy French. - Kai Guo; Xiaofeng He; Dengxue Lu; Yanping Zhang; Xiuzhuang Li; Zhiqiang Yan; Bo Qin (Natural Product Research, 2017)

Changes in endogenous hormones and H2O2 burst during shoot organogenesis in TDZ-treated Saussurea involucrate explants - Bin Guo; Wei He; Yan Zhao; Yandi Wu; Yanping Fu; Juan Guo; Yahui Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Impact of Biological Treatment Techniques on Perfluoroalkyl Acids Emissions in Municipal Sewage - Xinxuan Wang; Ruobing Zhang; Hong Zhang; Long He; Jincan Shen; Zhifang Chai; Bo Yang; Yanping Wang (Water, Air, & Soil Pollution, 2016)

Evidence of the Matthew effect in scientific research on mammals in the Chinese First-class National Protected Animals list - He Zhang; Yanping Hu; Yanming Zhang; Wenjing Li (Biodiversity and Conservation, 2015)

Exploring the Wnt Pathway-Associated LncRNAs and Genes Involved in Pancreatic Carcinogenesis Driven by Tp53 Mutation - Qi Wang; He Jiang; Chen Ping; Ruizhe Shen; Tingting Liu; Juanjuan Li; Yuting Qian; Yanping Tang; Shidan Cheng; Weiyan Yao; Lifu Wang (Pharmaceutical Research, 2015)

Inhibition of the Activation and Recruitment of Microglia-Like Cells Protects Against Neomycin-Induced Ototoxicity - Shan Sun; Huiqian Yu; Hui Yu; Mei Honglin; Wenli Ni; Yanping Zhang; Luo Guo; Yingzi He; Zhen Xue; Yusu Ni; Jin Li; Yi Feng; et al. (Molecular Neurobiology, 2015)

Orexin A attenuates the sleep-promoting effect of adenosine in the lateral hypothalamus of rats - Yanping Cun; Lin Tang; Jie Yan; Chao He; Yang Li; Zhian Hu; Jianxia Xia (Neuroscience Bulletin, 2014)

Composition and spectroscopic characteristics of dissolved organic matter extracted from the sediment of Erhai Lake in China - Yanping Li; Shengrui Wang; Li Zhang; Haichao Zhao; Lixin Jiao; Yali Zhao; Xiaosong He (Journal of Soils and Sediments, 2014)

Glycosylation analysis of recombinant neutral protease I from Aspergillus oryzae expressed in Pichia pastoris - Da Lei; Yang Xu; Qinghua He; Yifeng Pan; Bo Chen; Liang Xiong; Yanping Li (Biotechnology Letters, 2013)

Down-regulation of human cytomegalovirus UL138, a novel latency-associated determinant, by hcmv-miR-UL36 - Yujing Huang; Ying Qi; Yanping Ma; Rong He; Yaohua Ji; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2013)

The nuclear translocation of endostatin is mediated by its receptor nucleolin in endothelial cells - Nan Song; Yanping Ding; Wei Zhuo; Ting He; Zhiguang Fu; Yang Chen; Xiaomin Song; Yan Fu; Yongzhang Luo (Angiogenesis, 2012)

Human cytomegalovirus RL13 gene transcripts in a clinical strain - Mali Li; Yanping Ma; Yaohua Ji; Rong He; Ying Qi; Zhengrong Sun; Ning Wang; Shuang Gao; Qiang Ruan (Virus Genes, 2011)

Single nucleotide polymorphism of FSHβ gene associated with reproductive traits in Japanese flounder (Paralichthys olivaceus) - Feng He; Haishen Wen; Dahui Yu; Jifang Li; Bao Shi; Caifang Chen; Jiaren Zhang; Guoxiong Jin; Xiaoyan Chen; Dan Shi; Yanping Yang (Journal of Ocean University of China, 2010)

Transcription pattern of UL131A-128 mRNA in clinical strains of human cytomegalovirus - Zhengrong Sun; Gaowei Ren; Yanping Ma; Ning Wang; Yaohua Ji; Ying Qi; Mali Li; Rong He; Qiang Ruan (Journal of Biosciences, 2010)

Caveolin-1 restoration by cholesterol enhances the inhibitory effect of simvastatin on arginine vasopressin-induced cardiac fibroblasts proliferation - Shaowei Liu; Yanping He; Yufeng Dou; Haichang Wang; Ling Tao; Lianyou Zhao; Fujun Shang; Hui Liu (Molecular and Cellular Biochemistry, 2009)

Diagnostic value of HCMV pp65 antigen detection by FCA for symptomatic and asymptomatic infection: compared to quantification of HCMV DNA and detection of IgM antibody in infants - Zhengrong Sun; Xiangshi Ceng; Zhiqin Mao; Jidong Wang; Qing Liu; Yaohua Ji; Yanping Ma; Ying Qi; Rong He; Qiang Ruan (Medical Microbiology and Immunology, 2009)

Human cytomegalovirus UL145 gene is highly conserved among clinical strains - Zhengrong Sun; Ying Lu; Qiang Ruan; Yaohua Ji; Rong He; Ying Qi; Yanping Ma; Yujing Huang (Journal of Biosciences, 2007)